Design Evaluation Of Hydraulic Pumping Unit At Well Alf-04 Kawengan Field - Indarti, Adrian; Nasution, Alfisyahri (Universitas Wiralodra, 2024)
The methods of lifting fluid from the well to the surface consists of natural wells method and artificial lift method. One type of artificial lifting is Hydraulic Pumping Unit (HPU) method. In this case, well ALF-04 as the HPU well in Kawengan field which faces lower actual production compare to its theoritic production calculation then decided need to be redesigned. The objectives of redesigned is to reach optimum flow rate of the well. Recently actual flow rate of this well is 309.2 bfpd, and then the result of IPR calculation by Vogel shows the Q max is 957.25 bfpd, it means this well production is still feasible to be optimized till approximately 765.8 bfpd. After redesign calculation , obtained pump setting depth 755 m, plunger size of 2.5